2018
DOI: 10.4103/1673-5374.235085
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells: a promising candidate to treat neurological disorders

Abstract: Neurologic impairments are usually irreversible as a result of limited regeneration in the central nervous system. Therefore, based on the regenerative capacity of stem cells, transplantation therapies of various stem cells have been tested in basic research and preclinical trials, and some have shown great prospects. This manuscript overviews the cellular and molecular characteristics of embryonic stem cells, induced pluripotent stem cells, neural stem cells, retinal stem/progenitor cells, mesenchymal stem/st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(50 citation statements)
references
References 129 publications
0
50
0
Order By: Relevance
“…MSCs are studied for central nervous system and peripheral nervous system repairments [9]. For instance, differentiated functional neurons from MSCs were used in the studies targeting neurodegenerative diseases [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…MSCs are studied for central nervous system and peripheral nervous system repairments [9]. For instance, differentiated functional neurons from MSCs were used in the studies targeting neurodegenerative diseases [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Neurologic diseases are usually irreversible as a result of slow and limited neurogenesis in the brain. 23 Therefore, based on the regenerative capacity of stem cells, transplantation therapies of various stem cells have been tested in basic research with animal models, and preclinical and clinical trials, and many have shown great prospects and therapeutic promises. 23 Comparative studies have been raised to understand nature, properties, and number of donor stem cells, the delivery mode, and the selection of proper patient populations that may benefit from cell-based therapies.…”
Section: Stem Cells For Neurologic Diseasesmentioning
confidence: 99%
“…Despite significant advances in modern medicine, many diseases that increase the mortality or cause disabilities in the world's human population currently remain incurable. Due to their properties that allow them to be expanded indefinitely in vitro and to be differentiated into various somatic cell types, pluripotent stem cells (PSCs) hold significant potential for the development of cell-based therapies for a wide range of conditions, such as various neurodegenerative disorders, cancers, cardiac, and autoimmune diseases [1][2][3][4]. Moreover, the reprogramming of somatic cells to induced pluripotent stem cells (iPSCs) [5,6] has revealed an enormous potential for the development of personalized cell therapies, as autologous stem cells may minimize immunological incompatibilities while circumventing the ethical dilemmas associated with using embryo-derived stem cells (ESCs).…”
Section: Introductionmentioning
confidence: 99%